Student’s mathematical connection ability through GeoGebra assisted project-based learning model - Ari Septian (Jurnal Elemen, 2022)
Several previous studies related to mathematical connection abilities and GeoGebra-assisted project-based learning models, but this research focuses on improving students' mathematical connection ability in the Integral Calculus course.  This study examines the improvement of mathematical connection abilities through a project-based learning model assisted by GeoGebra. The research method used was a quasi-experimental design with a pretest-posttest nonequivalent multiple group design. The population is students of the Mathematics Education Study Program at the University in West Java, Indonesia. 1A and 1B students, which are used as samples. The technique of taking the research subject uses purposive sampling. The instrument consisted of a mathematical connection ability test with three essay questions. The test in this study used a pretest and posttest students' mathematical connection ability and the Group Embedded Figure Test (GEFT). The data analysis technique used an independent sample t-test and a two-way ANOVA test. The results showed that the improvement of students' mathematical connection ability who obtained the GeoGebra-assisted project-based learning model was better than students who obtained the project-based learning model. There is no interaction effect of learning models and cognitive styles on the achievement and improvement of students' mathematical connection abilities. The implication of this research is to provide significant changes in student learning habits in integral calculus courses to use technology and foster high self-regulated learning. This research has implications for universities implementing project-based learning models combined with other technology applications in other subjects.